Reflections on Roadkill between Mobility Studies and Animal Studies Altermobilities - Calarco, Matthew (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
Roadkill is a recurrent but often unthought feature of modern life. Yet, consideration of the broader significance of the myriad social, ethical, and political issues related to roadkill has largely gone missing from mainstream scholarship and activism. This neglect persists even in fields such as mobility studies and animal studies that would otherwise seem to have a vested interest in the topic. This book aims to bring roadkill to the foreground of current discussions among scholars and activists in these fields in order to demonstrate that roadkill is a uniquely important site from which to understand and contest the machinations of the dominant social order. It argues that a careful examination of roadkill can help both to uncover the hidden violence of contemporary human-centered systems of mobility and to develop alternative modes of mobility for a renewed social life in common with our more-than-human kin. Matthew Calarco is Professor of Philosophy at CaliforniaState University Fullerton, USA. He specializes in animal studies and environmental humanities, and brings philosophies and theories of mobility to bear on various aspects of research and teaching. .
Chapter 1. How (Not) to Look -- Chapter 2: What Is Roadkill? -- Chapter 3: Roadkill and Other Sacrificeable Lives -- Chapter 4: Subjects to Roadkill -- Chapter 5: Profaning the Streets.
Keywords: Philosophy of nature; Human ecology -- Study and teaching; Animal migration; Animal welfare -- Moral and ethical aspects; Critical theory; Philosophy of Nature; Environmental Studies; Animal Migration; Animal Ethics; Critical Theory